Exploring learner to content interaction as a success factor in online courses - Tekeisha Denise Zimmerman (Athabasca University Press, 2012)
Interaction plays a critical role in the learning process. For online course participants, interaction with the course content (learner-content interaction) is especially important because it can contribute to successful learning outcomes and course completion. This study aims to examine the relationship between learner-content interaction and course grade to determine if this interaction type is a contributing success factor. Data related to student interaction with course content, including time spent reviewing online course materials, such as module PowerPoint presentations and course videos and time spent completing weekly quizzes, were collected for students in three sections of an online course (N = 139). The data were then correlated against grades achieved in the course to determine if there was any relationship. Findings indicate statistically significant relationships between the amount of time the learner spent with the content and weekly quiz grades (r = .-72).  The study concludes that learners who spent more time interacting with course content achieve higher grades than those who spent less time with the content.